(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Human placental lactogen (HPL) is a pregnancy-related hormone produced by the placenta. The overall functions of serum HPL impacts the developing fetus and placenta. The objective of this study was to determine the relationship between maternal serum concentration of HPL and sonographic fetal growth parameters in pregnancy induced hypertension as a marker of placental function. This prospective cross-sectional study was conducted over a 9-month period in the University of Calabar Teaching Hospital, Calabar, Nigeria that involved 100 women with pregnancy induced hypertension. An obstetric ultrasound scan was done on all the subjects and their blood was collected for HPL evaluation using Enzyme-linked Immunosorbent Assay (ELISA). SPSS version 20 was used to analyze the data. Maternal serum HPL had a significant positive correlation with PLA (P=0.000), estimated gestational age (P=0.000), estimated fetal weight (P=0.000) and amniotic fluid index AFI (P=0.000) and a significant negative correlation with proteinuria (P=0.047), fetal heart rate (P=0.032) and HC/AC (P=0.000). It is concluded that maternal serum HPL concentration increases as pregnancy advances and causes a significant increase in placental thickness, fetal weight and amniotic fluid volume, however, its reduction is significantly associated with the onset of pre-eclampsia, fetal distress and asymmetrical intra-uterine growth restriction. Thus, the evaluation of maternal serum HPL concentration is a reliable marker of placental function in the second half of pregnancy